1998
DOI: 10.1111/j.1749-6632.1998.tb09618.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐Induced Neuroendocrine Modulation of Viral Pathogenesis and Immunitya

Abstract: Physical restraint (RST) was used to examine the interactions among the hypothalamic-pituitaryadrenal (HFA) axis, sympathetic nervous system, and the immune response to infection. In these studies, mice were infected with either herpes simplex virus (HSV) or influenza A/PR8 virus so that the impact of neuroendocrine activation could be assessed on disease pathophysiology and anti-viral immunity. RST suppressed lymphadenopathy in draining lymph nodes, reduced mononuclear cellular infiltration in the lungs, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 17 publications
3
76
1
2
Order By: Relevance
“…As described by van Endert and colleagues (23), peptide determinants are rapidly liberated from the fusion protein by Ub-hydrolases and behave like cytosolic minigene products. 6-OHDA treatment increased the primary T CD8ϩ response to Ova 257-264 and to the immunodominant VV determinant B8R [20][21][22][23][24][25][26][27] (Fig. 2B).…”
Section: -Ohda Treatment Of Host But Not Tcd8؉ Donor Enhances Antiviralmentioning
confidence: 91%
See 1 more Smart Citation
“…As described by van Endert and colleagues (23), peptide determinants are rapidly liberated from the fusion protein by Ub-hydrolases and behave like cytosolic minigene products. 6-OHDA treatment increased the primary T CD8ϩ response to Ova 257-264 and to the immunodominant VV determinant B8R [20][21][22][23][24][25][26][27] (Fig. 2B).…”
Section: -Ohda Treatment Of Host But Not Tcd8؉ Donor Enhances Antiviralmentioning
confidence: 91%
“…Previous studies by Sheridan et al have clearly demonstrated that the nervous system can have an impact on IAV responses (reviewed in ref. 20). In the present study, we address the role of the SNS in the generation of CD8 ϩ T cell (T CD8ϩ ) responses to viruses by investigating the effects of 6-OHDA treatment on well-defined mouse T CD8ϩ responses to viral and tumor antigens.…”
mentioning
confidence: 99%
“…Similar results were obtained after exposing rats to chronic restraint stress, whereas the administration of propanolol, a β-blocker, diminishes this effect (Hara et al 2013). Finally, the mutual action of GC and catecholamines (CA) during chronic restraint stress will simultaneously affect migration of mononuclear cells in the peripheral blood of a specific mouse strain (Hermann et al 1995), largely reduce cytokine expression from the lymph nodes and spleen (Dobbs et al 1996), delay cytokine gene transcription in the lungs and lymph nodes (Sheridan et al 1998), as well as diminish activation of cytotoxic T lymphocytes in the lymph nodes (Dobbs et al 1993;Sheridan et al 1998). However, it was also shown that chronic stressinduced changes in the concentrations of GC alone can have different effects on different pro-inflammatory cytokines, TNF-α, IL-1β and IL-6 (DeRijk et al 1997).…”
Section: Stress and The Immune Systemmentioning
confidence: 99%
“…Numerous studies have shown that exhausting physical activity and severe environmental and/or psychological stress have strong suppressive effects on the immune system [12]. Such suppression has significant implications for the susceptibility onset, course, and outcome of diseases such as cancer [13][14][15], autoimmunity [15,16] and infections [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…The immuosuppression resulting from chronic stress is due in part to a reduction in lymphocyte numbers [20][21][22]. Consequently, stress-induced lymphopenia has been observed in surgical patients [23], over-exercised athletes [24], persons under various psychological stresses [25,26], and animals subjected to physical restraint [15,27]. While several immune effects have been shown to be associated with stress, the exact mechanisms remain to be elucidated, especially in different organs of the immune system.…”
Section: Introductionmentioning
confidence: 99%